A destinação dos royalties minerais na lei orçamentária anual de Parauapebas de 2021 à luz dos objetivos de desenvolvimento sustentável - CUNHA, Lucas Ribeiro (2023)
The Financial Compensation for Mineral Exploration (FCME), or, simply, mineral royalties, is an patrimonial income owed to the Union by individuals or legal entities that realize mineral exploration. 60% of the total collected from CFEM is transferred to the city where these activities take place, as is the case of Parauapebas, in the state of Pará. Thus, the municipal government needs to allocate the resources from the CFEM in the Annual Budget Law (ABL), aiming at the intergenerational socioeconomic development of Parauapebas so that the city does not become dependent on the mining activity, because they are an exhaustible and scarce resource. For this to happen, the resources applied in the ABL must have the purpose of achieving the Sustainable Development Goals (SDGs), which are goals that seek the sustainable development of the planet. Through the deductive method and documental, theoretical and normative analysis of a qualitative-quantitative nature, based on works, articles and legislation, the objective of this research was to analyze how mineral royalties were allocated in the ABL of 2021 and if their destination fostered the meeting of SDGs. In terms of final considerations, it is concluded that the FCME resources were partially allocated by the LOA within the scope of the SDGs, since this Law did not allocate resources for the construction of SDGs 5, 7, 12 and 17, as well as not completely dealt with SDG 2